A highly selective and sensitive electrochemical determination of melamine based on succinic acid functionalized copper oxide nanostructures. Issue 127 (14th December 2015) - Soomro, Razium Ali; Hallam, Keith Richard; Ibupoto, Zafar Hussain; Tahira, Aneela; Jawaid, Sana; Hussain Sherazi, Syed Tufail; Sirajjuddin,; Willander, Magnus
Abstract : This study presents the development of a highly selective and sensitive electrochemical sensor for the determination of melamine from aqueous environments. Abstract : This study presents the development of a highly selective and sensitive electrochemical sensor for the determination of melamine from aqueous environments. The sensor system is based on functionalised marigold-like CuO nanostructures fabricated using a controlled hydrothermal process, where the utilised succinic acid is considered to play a dual role as a functionalising and growth controlling agent (modifier). The fabricated nanostructures exhibit sharp and well-ordered structural features with dimensions (thickness) in the range of 10–50 nm. The sensor system exhibits strong linearity within the concentration range of 0.1 × 10 −9 to 5.6 × 10 −9 M and demonstrates an excellent limit of detection up to 0.1 × 10 −10 M. The extreme selectivity and sensing capability of the developed sensor is attributed to the synergy of selective interaction between succinic acid and melamine moieties, and the high surface area of marigold-like CuO nanostructures. In addition to this, the developed sensor was also utilised for the determination of melamine from real milk samples collected from different regions of Hyderabad, Pakistan. The obtained excellent recoveries proved the feasibility of the sensor for real life applications. The sensor system offers an operative measure for detecting extremely low melamine content with high selectivity in food contents.